Nepali Domestic Workers in New Delhi: Strategies and Agency - Basnet, Chudamani; A. S., Sandhya (Dhaulagiri Journal of Sociology and Anthropology, 2019)
Scholars have noted deplorable conditions of female migrant workers who suffer several types of citizenship disabilities as most countries do not extend equal citizenship rights and protections to migrant workers. In addition to this, they are unable to take full advantage of the rights available to them in the host countries because of low cultural and social capital. Further, studies have emphasized how the breakdown of the traditional economy and the penetration of the market in developing societies have forced people, especially from rural areas, to seek low-paying dead-end jobs in the global labor market. Examining Nepali domestic workers in New Delhi, while this research agrees with the existing studies, we also bring to notice the fact that migrant female workers are not always passive victims and that they exercise considerable choice and agency. The case of Nepali domestic workers in New Delhi offers fresh insight into the ways in which migrant women attempt to actively influence and control the work conditions and immediate labour market outcomes. This paper also shows that even if Nepali migrant workers gain in a limited way, they actively collude with their employers to marginalize native domestic workers. In the end, traditional power relations and inequality are reproduced unchallenged.